O direito fundamental à previsibilidade das decisões judiciais e a proteção da confiança como consectários lógicos do estado democrático de direito - Torquato, Glacielle Borges (Universidade Federal do Tocantins, 2016)
The Brazilian legislation and the post-positivist judicial thought departed from the traditional model of strict legal conduct to the wider approach of the primacy of principles. General clauses and indeterminate legal concepts require of the administrator of the law to act within the scope of specific weighting. This broader textual stance on constitutional and infra-constitutional legislation came to require a hermeneutical activity leaning towards a case-by-case approach of administration of justice in the historical context of collectivization of judicial demands, which calls for compromise with the effect of binding precedent and the principle of legal certainty, in order to assure equality before judicial discretion. Reflective to those phenomena, the concept of civil law was gradually found insufficient, followed by a natural leaning towards that of the common law having the same rational decision process to legal cases of binding nature. The issue raised in the Brazilian legal order did not go unnoticed by the Commission on Reform of Civil Procedure Rules, which by the New Civil Procedure Code, enacted by the Law nº 13.105/2015, inaugurated the Incident of Resolution of the Repeated Demands so that the instability generated by the normative uncertainty could be conformed and legal cases of the same nature would have the same decisions. This research proposes to apply the innovations of the New Civil Procedure Code to the Internal Rule of the Tocantins Supreme Court – the central object of this dissertation – and to determine the way by which such instruments are to be implemented, mainly in assurance of a scenario of democratic and dialogical debate, based on rational arguments, as to ensure the stability of affirmed understandings and the materialization of the principles of legal certainty and equality.